Comparison of Compound and Single-Nutrient Fertilizer Sources on Cabbage Growth and Production - Hafith Furqoni (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
This study evaluated the effects of compound and single-nutrient fertilizers on the growth and yield of cabbage (Brassica oleracea L.). The experiment was conducted using a randomized complete block design with seven fertilization treatments, including varying doses of compound fertilizer and a single-nutrient control. Results showed that the application of a 1.0× dose of compound fertilizer significantly improved plant height at 3 and 4 weeks after transplanting (WAT), and increased leaf number at 5 WAT. Yield components, including yield per plant, per plot, and hectare, were significantly higher in the 1.0× treatment, with an average yield of 1.92 kg per plant—an increase of 86.4% and 11.6% compared to the control and single-nutrient treatments, respectively. The relative agronomic effectiveness of the 1.0× dose reached 139%, indicating superior performance over the standard fertilizer. Economic analysis confirmed its viability, with the highest benefit-cost ratio (R/C) of 2.23 and a net profit of IDR 14,487,900. These findings suggest that compound fertilizer is both agronomically effective and economically profitable. The recommended application rate for cabbage is 211 kg/ha, applied one week after transplanting.